Model dan Etika Pengambilan Keputusan dalam Kepemimpinan Lembaga Pendidikan Islam - Ubaidah Qoriatus Zahidah; Rofiatul Azkiyah; Firman Kurniawan; Mu’alimin (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study examines decision-making models and ethics in the leadership of Islamic educational institutions through a qualitative literature review approach. The research focuses on identifying and analyzing decision-making processes that integrate Islamic values, such as deliberation (syura), justice, honesty (as-siddiq), and trustworthiness (amanah). Data were collected from SINTA-indexed journal articles published between 2019 and 2024, with keywords including "decisionmaking," "leadership," and "educational institutions." The findings highlight that effective decision-making in Islamic education requires a balance between rational managerial models (e.g., bounded rationality) and ethical principles derived from Islamic teachings. Leaders must act as entrepreneurs, problem solvers, and mediators while upholding moral accountability. The study underscores the importance of ethical leadership in fostering transparent, collaborative, and integrity-driven educational environments. However, further research is needed to systematically integrate Islamic ethical frameworks into contemporary educational management practices.